Food Security in West Java Through the Lens of Traditionalist Paradigm: A Discourse Analysis - Ivan Chofyan; Ina Helena Agustina; Riswandha Risang Aji; Diden Rosenda; Rahmat Lazuardi (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2025)
Abstract. Food security begins with a world view regarding concerns about food shortages. This indication is also supported by the symptoms of global climate change. The Indonesian government through the 1945 Constitution and the 1996 Rome Declaration stipulates that one of the human rights is the fulfillment of food needs. West Java is part of the Indonesian government and has harmonized regulations for the fulfillment of food. The perspective of food security originating from the world view of science shows the need for support from different paradigms. West Java has a long-rooted cultural heritage of food security. The substantive World View of Food Security Science requires a traditionalism paradigm as a network support towards food security integration. The purpose of the study is to describe the substitution of the traditionalism paradigm for food security. The approach method is carried out through a discourse approach. Data collection through literature studies while analysis is carried out through discourse analysis through text and context of how the traditionalism paradigm builds, articulates and frames food security. The analysis stages identified three interrelated discourses, namely (1) West Java Food Security as part of the scientific world view (2) Traditionalist paradigm showing human manners towards food (3) West Java Food Security within the framework of the traditionalist paradigm.